Rational expectations and the end of macroeconomics - Wallace, Neil (1996)
The author discusses the impact of expectations on the "style of theorizing about macroeconomics". He states that one might almost say that the style associated with Keynes and his General Theory had ended. Static models based on relationships between aggregates and prices would be replaced by models capable of taking into account -thanks to reasonable expectations- the temporary applicability of economic decisions and the need to design micro-economic balances across the board. The author concludes by suggesting a number of guidelines for designing better curriculums for university economics study.